Human primary cementoblasts respond to combined IL-1β stimulation and compression with an impaired BSP and CEMP-1 expression - Diercke, Katja; Lux, Christopher J.; Erber, Ralf (European journal of cell biology, 2012)
Cementoblasts are cells that produce, secrete and direct the production of cementum. Resorption lacunae occur in over 90% of teeth at the compression side of the periodontal ligament and might result in an irreversible loss of the original root length. We isolated and cultivated human primary cementoblasts and investigated their expression pattern concerning markers of the osteoblastogenic differentiation (RUNX2, OCN, ALP, and BSP) and CEMP-1. Compared to osteoblasts, cementoblasts displayed an expression pattern comparable to osteoblasts in an early stage of osteoblastogenic differentiation. Next, the human primary cementoblasts were stimulated with IL-1␤ (1 and 10 ng/ml) for 24 and 96 h and subsequently subjected to compressive forces (30.3 g/cm2) for 1 and 6 h. Our in vitro data demonstrated that BSP and CEMP-1 expression signiﬁcantly decreased when stimulation was accompanied by compression, while compression or stimulation alone led to increased levels of BSP and decreased levels of CEMP-1. We concluded that human primary cementoblasts subjected to compression and IL-1␤ stimulation impeded BSP and CEMP-1 expression, proteins that are associated with cementogenesis.